Impact of multimorbidity on long-term outcomes in older adults with non-ST elevation acute coronary syndrome in the North East of England: a multi-centre cohort study of patients undergoing invasive care. Issue 7 (26th July 2022) - Beska, Benjamin; Mills, Greg B; Ratcovich, Hanna; Wilkinson, Chris; Damluji, Abdulla A; Kunadian, Vijay
Abstract : Objectives: Older adults have a higher degree of multimorbidity, which may adversely affect longer term outcomes from non-ST elevation acute coronary syndrome (NSTE-ACS). We investigated the impact of multimorbidity on cardiovascular outcomes 5 years after invasive management of NSTE-ACS. Design: Prospective cohort study. Setting: Multicentre study conducted in the north of England. Participants: 298 patients aged ≥75 years with NSTE-ACS and referred for coronary angiography, with 264 (88.0%) completing 5-year follow-up. Main outcome measures: Multimorbidity was evaluated at baseline with the Charlson comorbidity index (CCI). The primary composite outcome was all-cause mortality, myocardial infarction, stroke, urgent repeat revascularisation or significant bleeding. Results: Mean age was 80.9 (±6.1) years. The cohort median CCI score was 5 (IQR 4–7). The primary composite outcome occurred in 48.1% at 5 years, at which time 31.0% of the cohort had died. Compared with those with few comorbidities (CCI score 3–5), a higher CCI score (≥6) was positively associated with the primary composite outcome (adjusted HR (aHR) 1.64 (95% CI 1.14 to 2.35), p=0.008 adjusted for age and sex), driven by an increased risk of death (aHR 2.20 (1.38 to 3.49), p=0.001). For each additional CCI comorbidity, on average, there was a 20% increased risk of the primary composite endpoint at 5 years (aHR 1.20 (1.09 to 1.33), p<0.001). Conclusions: In older adults with NSTE-ACS referred for coronary angiography, the presence of multimorbidity is associated with an increased risk of long-term adverse cardiovascular events, driven by a higher risk of all-cause mortality. Trial registration number: NCT01933581 ; ClinicalTrials.gov.